Semantic challenges to realism : Dummett and Putnam - Gardiner, Mark Q. (Mark Quentin), 1963- (University of Toronto Press, 2000)
Although many philosophers espouse anti-realism, the only sustained arguments for the position are due to Michael Dummett and Hilary Putnam. Gardiner's unpretentious style and lucid organization make sense of Dummett's and Putnam's discourse.
Keywords: Dummett, Michael, -- 1925-2011.; Putnam, Hilary.; Dummett, Michael, -- 1925-2011; Putnam, Hilary; Dummett, Michael A. E.; Realism.; Semantics (Philosophy); Réalisme.; Sémantique (Philosophie); PHILOSOPHY -- Movements -- Realism.; PHILOSOPHY -- History & Surveys -- Modern.; Realism; Realismus -- Philosophie; Electronic books.; e-books.; Livres numériques.